Korelasi Gaya Kepemimpinan Kepala Madrasah Dan Motivasi Kerja Guru Terhadap Kinerja Guru Di Madrasah Aliyah Negeri 3 Nganjuk - Solikatun; Uswatun Hasanah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
As educators, teachers must be able to improve their performance in carrying out tasks. To achieve high teacher performance, one of them is the motivation factor. Motivation is the driving force for someone to do an activity that is manifested in the form of a real action. Thus the higher the motivation of someone, the higher the performance and vice versa, the lower the motivation of a person, the lower the performance. The success of teacher performance will be seen if there is motivation from the teacher himself and has the support of the madrasa headmaster. Therefore, in addition to the teacher himself who is trying to improve the quality of his performance, the madrasa also seeks to establish good leadership as an empowerment of teachers and madrasa members so that they have good performance in carrying out their duties. This type of research is quantitative research that aims to find answers about the questions in the research based on the actual situation so that it is obtained about the prevailing picture in relation to the correlation between the leadership style of madrasah leaders and teacher work motivation on teacher performance in MAN 3 Nganjuk. The conclusions based on data analysis are: Madrasah headship leadership and teacher work motivation together have positive and significant influence on teacher performance. Good madrasah head leadership and high teacher work motivation will make teachers increasingly improve performance in carrying out their duties.